Assemblage of spiders diversity - an agent of biological control of agricultural pests - Veeramani A; Abinaya D; Ennavan V; Bhuvaneshwaran N; Ravichandran S; Pazhanisamy S (Journal of Applied Entomologist, 2023)
Arachnids provide an important service by keeping insect populations under control. Spiders are acting as an agent of biological control of insects; without them many insects would have reached high level of pest proportions. This present investigation was aimed to attain the diversity of spider fauna of cultivated croplands of Swamimalai Region of Cauvery Delta, Tamil Nadu. The data on diversity of spiders was investigated by hand picking method. The spotted spider specimens were photographed and left in the same environment without disturbing it. A total of 31 species of spiders under 13 genera were recorded in buildings, wooded areas and cultivated regions. Spiders are normally built nests on their living habits for dwelling as well as catching prey which are trapped in their nests. This is only the baseline study but it needs a long-term inventory which will fulfill the lacunae of spider diversity in the study area.